Age and Working Hours as Predictors of Hearing Loss Among Workers in a High-Noise Glass Factory in Indonesia: A Cross-Sectional Study - Hotmaria Agustina Pakpahan; Evi Ulina Margareta Situmorang; Hadiyanto Usman; Gunterus Evans; Lonah Lonah (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: This study aims to address the gap by investigating the factors associated with hearing loss among industrial workers at a high-quality glass factory located in the Cikarang Industrial Area, Bekasi. Methods: A descriptive-analytic study with a cross-sectional design was conducted in 2023, involving 101 industrial workers aged 36.7 ± 10.1 years old with 54 men and 47 women at PT X, Cikarang, Bekasi. The total population consisted of 159 workers, based on the Slovin formula, a sample of 101 respondents was obtained. The sample was selected using a simple random sampling technique. Data were analyzed using SPSS version 22 for Windows with Chi-square and multiple logistic regression tests. Results: Significant associations were found between hearing loss and the following factors: age, noise exposure intensity, working hours, length of employment (p<0.05). Multivariate logistic regression analysis showed that age ?40 years (aOR=41.65; 95% CI: 11.19–154.97) and extended working hours (aOR=5.63; 95% CI: 1.50–21.07) were significant independent predictors of hearing loss. Although occupational noise exposure showed a significant association in bivariate analysis, its effect was attenuated after adjustment for other variables, suggesting potential interrelationships among occupational risk factors and hearing impairment. Conclusion: Noise-induced hearing loss (NIHL) among industrial workers in PT X, Cikarang, Bekasi is significantly associated with age and working hours, after controlling for noise exposure intensity, nutritional status, length of employment and the use of hearing protection devices (HPDs). Therefore, the company is advised to develop a comprehensive hearing conservation program that includes regulated working hours, regular health check-ups, job rotation, training and supervision on the proper use of HPDs, and the implementation of engineering controls to reduce noise at its source.